2017
DOI: 10.1111/jpi.12417
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin successfully rescues hippocampal bioenergetics and improves cognitive function following drug intoxication by promoting Nrf2‐ARE signaling activity

Abstract: Prolonged exposure to gamma-hydroxybutyric acid (GHB) would cause drug intoxication in which impaired cognitive function results from enhanced hippocampal oxidative stress may serve as a major symptom in this deficiency. Considering melatonin possesses significant anti-oxidative efficacy, this study aimed to determine whether melatonin would successfully promote the nuclear factor erythroid 2-related factor 2 and antioxidant responsive element (Nrf2-ARE) signaling, depress oxidative stress, and rescue hippocam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 70 publications
2
24
0
Order By: Relevance
“…It is generally accepted that the dose and dosing time are highly related to the efficacy of the pharmacological action of melatonin. The dose of 10 mg/kg ip (which produces far higher melatonin levels than normal physiological concentrations in the body) and the dosing time (9:00 am-9:30 am) used for melatonin treatment in the present study are comparable with those used in previous studies [64][65][66] and have been proven to be effective. It has been reported that melatonin can be tolerated at large doses by healthy humans and subjects with Parkinson's disease without any severe adverse effects.…”
Section: F I G U R E 1supporting
confidence: 66%
“…It is generally accepted that the dose and dosing time are highly related to the efficacy of the pharmacological action of melatonin. The dose of 10 mg/kg ip (which produces far higher melatonin levels than normal physiological concentrations in the body) and the dosing time (9:00 am-9:30 am) used for melatonin treatment in the present study are comparable with those used in previous studies [64][65][66] and have been proven to be effective. It has been reported that melatonin can be tolerated at large doses by healthy humans and subjects with Parkinson's disease without any severe adverse effects.…”
Section: F I G U R E 1supporting
confidence: 66%
“…Melatonin has an antioxidative property and scavenges free radicals more effectively than do vitamins C and E (Korkmaz et al, ; Pieri, Marra, Moroni, Recchioni, & Marcheselli, ). Melatonin has positive effects about the hippocampus‐dependent cognitive function (Chen et al, ) as well as the hippocampal neurogenesis (Iggena, Winter, & Steiner, ; Yoo, Kim, Lee, et al, ; ). Additionally, it increases the number of proliferating cells and neuroblasts in the dentate gyrus of aged mice induced by D‐galactose treatment (Yoo, Kim, Lee, et al, ; ).…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin has positive effects about the hippocampus-dependent cognitive function (Chen et al, 2017) as well as the hippocampal neurogenesis (Iggena, Winter, & Steiner, 2017;Yoo, Kim, Lee, et al, 2012;). Additionally, it increases the number of proliferating cells and neuroblasts in the dentate gyrus of aged mice induced by Dgalactose treatment (Yoo, Kim, Lee, et al, 2012;).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, by activating the NRF2 signaling pathway, hydralazine induces stress resistance and extends the lifespan of Caenorhabditis elegans . Melatonin effectively rescues hippocampal bioenergetics through depressing the oxidative stress by promoting NRF2 molecular machinery . Additionally, to improve bladder function and to decrease the apoptosis of the bladder in STZ‐induced diabetic rats, Grape seed proanthocyanidin extract (GSPE) activated the NRF2 defense pathway and upregulated downstream hemeoxygenase‐1 (HO‐1) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that cisplatin‐induced cystopathy was also associated with the neurogenic lesions, so we examined NGF whose mRNA expression was regulated by NRF2 in glioblastoma cells and normal human astrocytes and found NGF was significantly upregulated in the Cis‐Cur group compared with the Cis group. Also, the increased expression of NGF induced by activation of the NRF2 pathway was reported to promote neurite outgrowth .…”
Section: Discussionmentioning
confidence: 99%